Factors governing when a metal-bound water is deprotonated in proteins. Issue 47 (22nd November 2018) - Grauffel, Cédric; Lim, Carmay
Abstract : We evaluate the extent to which the p K w depends on the type, number, and metal-binding mode of the first-shell ligands, the metal–ligand bond distances, first-shell⋯second-shell H-bonding interactions, and the protein environment. Abstract : Understanding when a metal-bound water molecule in a protein is deprotonated is important as this affects the charge distribution in the metal-binding/enzyme active site and thus their interactions, the enzyme mechanism, and inhibitor design. The protonation state of the metal-bound water molecule at a given pH depends on its p K a value, which in turn depends on the properties of the cation, its ligands, and the protein environment. Here, we reveal how and the extent to which (i) the first-shell composition (type, charge, and number of ligands), (ii) the metal site's immediate surroundings (first-shell⋯second-shell hydrogen-bonding interactions, metal–ligand distance constraints, and ligand-binding mode) and (iii) the protein architecture and coupled solvent interactions (long-range electrostatic interactions and solvent exposure of the site) affect the Zn 2+ -bound water p K a . The results, which are consistent with available experimental p K a values of Zn 2+ -bound water, provide guidelines to predict when Zn 2+ -bound water would likely be deprotonated at physiological pH.